A randomized controlled study comparing incision and drainage with deroofing versus saucerization for the treatment of carbuncle - Khalid, Shahril; Tan, Guan Hee; Bong, Jan Jin; Othman, Hairol Azrin; Wan Jamaludin, Wan Fariza; Jarmin, Razman (Faculty of Medicine, 2025)
Saucerization is a common treatment for carbuncle in Malaysia but is associated with excessive bleeding and prolonged healing. Incisional and drainage (I&D) is recommended internationally, however it is not widely practiced locally partly due to lesion severity at presentation. We compared I&D with deroofing against saucerization to treat carbuncle. We prospectively analyzed 59 patients in a single center for two years duration. All analysis was done based on intention to treat. Forty-four patients were eligible and randomized to I&D with deroofing arm (n=21) or saucerization arm (n=23). Continuous variables were analyzed using T-test for independent sample, while where distributions were skewed and logarithmic transformation did not increase normality, Mann Whitney test was applied. Differences in categorical variables were compared using Chi square test. I&D with deroofing was associated with shorter healing time (median 28 days vs 72 days, p=0.003) and less days requiring dressing change (median 28 days vs 77.5 days, p=0.002). Saucerization was observed to have higher complications (17.4%; 3 patients required de-sloughing under local and general anesthesia, 1 required blood transfusion), while I&D with deroofing was observed to have less complications (14.3%; 3 patients required further de-sloughing under local anesthesia) with shorter operating times although these were not statistically significant. Staphylococcus aureus was the commonest organism grown from swab cultures from both arms I&D with deroofing should be the treatment of choice in carbuncle due to significant improvement in healing time and less days required for dressing change. Future studies on cost effectiveness and effects of age, diabetes, incisional approach and lesion size on wound healing and sepsis resolution will provide a better insight on the holistic management of carbuncle.